Conceptualization Of Meaningful Participation As An Instrument For Participatory Legal Awareness Building - Alfian Reymon Makaruku; Eivandro Wattimury; Sostones Y. Sisinaru (UNIVERSITAS PAKUAN, 2026)
Low levels of legal awareness are often caused by a lack of public involvement in the processes of law-making and law enforcement. This study analyses the impact of meaningful participation on the development of legal awareness and conceptualises meaningful participation as a means of fostering legal awareness. It employs a normative legal methodology, utilising both conceptual and statutory approaches. The findings indicate that the concept of meaningful participation in fostering legal awareness can transform technical compliance into the internalisation of values and voluntary compliance with the law, build a participatory and responsive culture of legal compliance, and integrate the enhancement of legal awareness with the practice of deliberative democracy, thereby fostering a sense of ownership of the law. Furthermore, realising “meaningful participation” as an instrument for fostering legal awareness can be achieved through; the provision of access to adequate information, public legal education within inclusive consultative forums, the consistent use of digital technology coupled with accountable evaluation mechanisms, and cross-sectoral collaboration to enhance responsive legal awareness. Keywords: Meaningful Participation, Instrument, Legal Awareness.